Syphilitic infection impairs immunity by inducing both apoptosis and pyroptosis of CD4 and CD8 T lymphocytes - Wei Xia; Jinxue Zhao; Bin Su; Yanmei Jiao; Wenjia Weng; Ming Zhang; Xiaodan Wang; Caiping Guo; Hao Wu; Tong Zhang; Yanqing Gao; Zaicun Li (Innate Immunity, 2021)
Syphilis is an important health problem worldwide; however, few studies have probed the impact of syphilitic infection on T cell turnover. The mechanisms behind the frequency of T cell subset changes and the associations between these subsets during syphilitic infection remain unclear. Herein, we used a cell-staining method and flow cytometry to explore changes in T cell subpopulations and potential contribution of apoptosis and pyroptosis that triggered therein. We investigated caspase-1-mediated pyroptosis and caspase-3-mediated apoptosis of CD4 + and CD8 + T cells, the major effector lymphocytes with pivotal roles in the pathogenesis of infectious diseases. We found that the levels of caspase-1 and caspase-3 increased in both the circulation and intracellularly in CD4 + and CD8 + T cells. Caspase-1 showed a continual increase from early latent stage infection through to phase 2 disease, whereas caspase-3 increased through to phase 1 disease but declined during phase 2. In addition, serum levels and intracellular expression of caspase-1 and caspase-3 were positively correlated. Overall, this study increases our understanding of how syphilitic infection influences CD4 + and CD8 + T-cell turnover, which may help with designing novel and effective strategies to control syphilis infection and prevent its transmission.